Clinically Probable REM Sleep Behavior Disorder and Other Non‐Motor Symptoms in Progressive Supranuclear Palsy: Prevalence and Associated Clinical Features - Neeraj Balaini; Paras Borse; Manu Santhappan Girija; Reji Paul; Aimy Hynse; Asha Kishore (Movement Disorders Clinical Practice, 2026)
Abstract Background REM sleep behavior disorder (RBD) is now increasingly recognized in progressive supranuclear palsy (PSP), with unclear clinical relevance. Objectives To determine the frequency of pRBD and non‐motor symptoms in PSP and association between the two. Methods We enrolled 150 consecutive patients with PSP and 150 age‐ and sex‐matched controls. Probable RBD (pRBD) was identified using the REM Sleep Behavior Disorder Screening Questionnaire. Clinical, cognitive, and NMS scores were measured using validated rating scales. Group comparisons and regression analyses were performed. Results The mean age at study was 69.1 ± 7.5 years, pRBD was identified in 18.7% of patients with PSP and in none of the controls. Patients with pRBD had a greater NMS burden ( p < 0.001) and poorer quality of life ( p = 0.041). Attention/memory ( β = 0.196, p = 0.015) and gastrointestinal symptoms ( β = 0.255, p = 0.003) independently predicted pRBD. Conclusions pRBD is a common non‐motor feature of PSP and is associated with greater non‐motor symptom burden and poorer quality of life.